Computerized Neurocognitive Testing within 1 Week of Sport-Related Concussion: Meta-analytic Review and Analysis of Moderating Factors. (13th February 2014) - Kontos, Anthony P.; Braithwaite, Rock; Dakan, Scott; Elbin, R.J.
Abstract The purpose of this study is to perform a meta-analysis assessing the effects of sport-related concussion as measured by computerized neurocognitive tests (NCT) 1-week post injury. Thirty-seven studies involving 3960 participants between 2000 and 2011 were included. Hedge's g provides an adjusted effect size for smaller sample sizes and was calculated for overall and cognitive task effects, and subgroup analyses were conducted for age, type of NCT, and sport. Concussions had a low negative effect (g = −0.16; p < .001) across all groups, outcomes, and time points. Code substitution (g = −0.27; p < .05), visual memory (g = −0.25; p < .05), processing speed (g = −0.18; p < .05), and memory (g = −0.21; p < .05) tasks demonstrated negative effects for concussion. Younger adolescents had lower (g = −0.29; p < .05) NCT performance than older adolescents (g = −0.01) and college aged athletes (g = −0.11). ImPACT studies (g = −0.19; p < .05) demonstrated a negative effect for concussion as did those involving contact sports (g = −0.20; p < .05). A low to moderate overall effect size of concussion on neurocognitive performance was supported. Subgroup analyses revealed different effect sizes for specific cognitive tasks, types of NCTs, age, and type of sport. (JINS, 2014, 20, 1–9)